2019
DOI: 10.1590/1678-4685-gmb-2018-0197
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone insensitivity (Laron syndrome): Report of a new family and review of Brazilian patients

Abstract: Laron's syndrome (LS) is a rare genetic disorder characterized by insensitivity to growth hormone (GH). Up to the present time, over 70 mutations of GH receptor (GHR) gene have been identified leading to GH/insulin-like growth factor type 1 (IGF1) signaling pathway defect. The number of LS patients worldwide is unknown, as many are probably undiagnosed. We report two sibs from a consanguineous family from Minas Gerais, southeastern Brazil. The parents have three children. The older, a 4-years-old girl was 80.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
0
10
0
3
Order By: Relevance
“…1 ). These patients are concentrated in the Mediterranean area, southern Ecuador, and South America, with a similar gender distribution ( 10 ). The main features of the included studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). These patients are concentrated in the Mediterranean area, southern Ecuador, and South America, with a similar gender distribution ( 10 ). The main features of the included studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the purpose of this systematic review is to analyze the evidence collected over the years on this topic in patients with Laron syndrome, to highlight the effects of low IGF1 on the human HPT axis. Particularly, the These patients are concentrated in the Mediterranean area, southern Ecuador, and South America, with a similar gender distribution [10]. The main features of the included studies are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The number of known and/or published LS patients is around 350. Most cases have been reported from the Mediterranean region and Southern Ecuador, and a few cases from South America, as recently reviewed [ 59 , 60 , 61 ]. LS is characterized by insensitivity to GH.…”
Section: Nutrient Sensors That Potentially Affect Health Spanmentioning
confidence: 99%
“…The biochemical features typical of LS patients are high serum level of GH and low free IGF1 concentrations. People affected by LS are characterized by dwarfism and obesity and have a tendency to develop hyperlipidemia, but surprisingly have a very low risk to manifest aging-related pathologies such as diabetes and cancer [ 59 , 62 , 63 ]. Additionally, other studies in humans showed a positive association between low IGF1 activity and longevity [ 64 ].…”
Section: Nutrient Sensors That Potentially Affect Health Spanmentioning
confidence: 99%
“…Subsequentemente, defeitos no gene do receptor de GH (GHR, MIM*600946) também foram descritos como causadores da Síndrome de Laron (MIM#262500), uma forma completa de Insensibilidade ao GH, além de formas parciais desta resistência hormonal (MIM#604271) 38,42 .…”
Section: Defeitos Nos Genes Do Eixo Gh-igfsunclassified